ANALISIS PENENTUAN LUAS PRODUKSI PADA PERUSAHAAN ROTI BANGKIT JAYA DI KOTA KUPANG - Raimundus Ivan Naisoko; Christien C Foenay; Antonio E L Nyoko (Journal of Management Small and Medium Enterprises (SMEs), 2020)
The purpose of this study is to analyze the determination of production volume to maximize profits.This research is a quantitative research. Data analysis techniques are Forecasting and LinearProgramming (Simplex Method). The result of analysis concluded that the production volume usingLinear Programming simplex method obtained in 2019 should produce as many as 405,792,000molten chocolate bread per year and by 2020 should produce as many as 4,107,480 molten chocolatebread per year for earning maximum profit. Meanwhile, the Forecasting result is to produce 4 typesof bread as many as 6,308,240 breads in 2019 and 6,365,560 breads in 2020. In terms of profitoptimization then calculation using Linear Programming is better however considering the marketingaspect where consumers require a variety of bread flavors then calculation using forecasting method ismore recommended. Keywords: Forecasting, Linear Programming, Optimization, Volume Production